Orientation system for people with cognitive disabilities - Ramos, João (2013)
In health care there has been a growing interest and investment in new tools to have a constant monitoring of patients. The increasing of average life ex-pectation and, consequently, the costs in health care due to elderly population are the motivation for this investment. However, healthmonitoring is not only important to elderly people, it can be also applied to people with cognitive disabilities. In this article we present some systems, which try to support these persons on doing their day-to-day activities and how it can improve their life quality. Also, we present an idea to a project that tries to help the persons with cognitive disabilities by providing assistance in geo-guidance and keep their caregivers aware of their location.